Potency of Palm Oil Plantation and Mill Byproduct as Ruminant Feed in Paser Regency, East Kalimantan - Hamdi Mayulu; S Sunarso; C. I. Sutrisno; S Sumarsono; M Christiyanto; K. Isharyudono (International Journal of Science and Engineering, 2013)
By-product produced from plantation and palm oil mill can be utilized for energy and protein source of ruminant feed. Thus, it still has potency for further exploration. The objective of the research was to investigate the nutrient value of palm oil plantation and mill’s by-product used to formulate ruminant feed. The research located in 66,118.5 ha of palm oil plantation in Paser regency, East Kalimantan province. The research was carried out in palm oil plantation and mill of PTPN XIII comprising productive plants (TM) in +14,000 ha arranged in 9 divisions (afdeling). Measured variables consisted of: 1) dry mass production (mass of midrib every cutting and frond) (kg);                        2) Centrosema sp mass production (kg); 3) mass of empty fruit bunches (kg); palm pressed fiber (PPF) (kg), palm kernel cake (PKC) (kg) dan palm oil sludge (POS) (kg); 4) nutrient content analyzed under proximate analysis in accordance with the procedure of Ruminant Feed Nutrient Laboratory, Faculty of Livestock, Diponegoro University. The result showed that total dry matter (DM) production was 14.82 ton/ha/year, consisting: midrib 29.09% (crude protein (CP) 3.16% and crude fiber (CF) 37.85%), frond 10.31% (CP 6.53% dan CF 30.39%), Centrosema sp. 2.48% (CP 22.58% and CF 35.12), EFB 24.31% (CP 7.01% and CF 40.22%), PPF 1.23% (CP 5.56% and CF 50.36%), PKC 1.29% (CP 15.49% and CF10.45) and POS 1.20% (CP 17.86% and CF 45.99%). This could be concluded that palm oil plantation and mill’s by-product was recommended for ruminant feed as it had huge amount and appropriate nutrient contentDoi: 10.12777/ijse.5.2.56-60 [How to cite this article: Mayulu, H., Sunarso, C. I. Sutrisno, Sumarsono, M. Christiyanto, K. Isharyudono. (2013).  Potency of Palm Oil Plantation and Mill Byproduct as Ruminant Feed in Paser Regency, East Kalimantan, 5(2),56-60. Doi: 10.12777/ijse.5.2.56-60]